Second foreign language learning strategies and their variations across language proficiency levels among Iranian EFL learners (Estrategias de aprendizaje del segundo idioma y su variación a través de niveles de competencia en los alumnos Iraníes de EFL) - Pazhakh, A.R. (Facultad de Contaduría Pública y Administración U.A.N.L., 2006)
Resumen. Este estudio se intenta determinar la relación entre las estrategias empleadas para aprendizaje del idioma. Además, trata de ver qué estrategias útiles se usan para el aprendizaje correspondiente con la competencia de los idiomas. Un test simulado de TOEFL (REA, 1993) fue utilizado. El inventario de estrategia de Oxford (Oxford, 1990) fue usado para estimar la frecuencia de estas estrategias. Estos resultados como los anteriores sobre este tema confirman una relación directa entre estas estrategias y los niveles de la competencia y además, presentan los tipos de estrategias adoptadas por los niveles avanzados, intermedios y básicos. Resultados sugieren el uso de estrategias compensatorias mego-cognoscitivas para los niveles avanzados de los aprendices para elevar el nivel de competencia. Abstract. The present study has attempted to determine weather there is any relationship between language learning strategies employed by language learners, and if so what relationship exists between them. Furthermore, it has tried to investigate what effective and useful strategies the learners employ while learning English as a foreign language correspondent with their proficiency levels. A simulated TOEFL (REA, 1993) test was initially administered to classify the learners into three classes of proficiency levels. Oxford‟s Strategy Inventory, SILL, (Oxford, 1990) was used to determine the frequency of the language learning strategies applied by learners. The results of this study provide confirmation of previous research findings concerning the direct relationship between language learning strategies and language proficiency level, and represent the types of the strategies adopted by advanced, intermediate and elementary language learners. The implications of this study are to suggest both the metacognitive compensatory strategies, the most frequent strategies employed by advanced learners be instructed to the language learners in order to upgrade their proficiency level.